2012
DOI: 10.14411/eje.2012.034
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic bacteria (Erwinia sp.) in the gut of Frankliniella occidentalis (Thysanoptera: Thripidae) do not affect its ability to transmit tospovirus

Abstract: Abstract. Tomato spotted wilt virus (TSWV) is one of the most harmful plant viruses and one of its most important vectors is the western flower thrips [Frankliniella occidentalis Pergande (Thysanoptera: Thripidae)]. Recently, we reported the close association of Erwinia sp. gut bacteria with this species of thrips. The first instar larvae acquire these bacteria from their food source. A high proportion of adult western flower thrips transmit TSWV after acquiring the virus during the first larval stage when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Erwinia, Pantoea, Enterobacter, Serratia, Escherichia and Pseudomonas have been identified internally from thrips (de Vries et al 2001a; Gitaitis et al 2003; Chanbusarakum & Ullman 2008; de Vries et al 2008; de Vries et al 2012). Erwinia herbicola and Enterobacter agglomerans have been synonymized with Pantoea agglomerans so these 3 genera identified in chilli thrips could represent a single taxon found in association with several insects (Medina et al 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Erwinia, Pantoea, Enterobacter, Serratia, Escherichia and Pseudomonas have been identified internally from thrips (de Vries et al 2001a; Gitaitis et al 2003; Chanbusarakum & Ullman 2008; de Vries et al 2008; de Vries et al 2012). Erwinia herbicola and Enterobacter agglomerans have been synonymized with Pantoea agglomerans so these 3 genera identified in chilli thrips could represent a single taxon found in association with several insects (Medina et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Thrips on the whole have received little attention regarding this important aspect of arthropod ecology. Previous work has largely focused on the most frequently encountered bacterium (identified as a near- Erwinia species) within a single thrips species, the Western flower thrips Frankliniella occidentalis (de Vries et al 2001a; de Vries et al 2001b; de Vries et al 2004; de Vries et al 2006; Chanbusarakum & Ullman 2008, 2009; de Vries et al 2012) with a few studies on other species (Wells et al 2002; Gitaitis et al 2003; de Vries et al 2008). …”
mentioning
confidence: 99%
“…The different genomic components of the thrips holobiont are beginning to be unveiled: recently, the genome of WFT and that of the melon thrips ( T. palmi ) were characterized ( 37 , 38 ); the bacteria associated with thrips were also partially characterized in the case of WFT ( 39 41 ). Regarding the viral component of the thrips microbiome, knowledge is still very limited: a recent work described viruses associated with soybean thrips samples from various U.S. regions ( 16 ); furthermore, four genomovirus genomes were amplified from Echinothrips americanus (Morgan), a pest thrips sampled in Florida ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…occidentalis and T . tabaci 30 , 32 , 34 , 35 , 73 , while Agrobacterium , Methylobacterium and Pseudomonas have been identified from S . staphylinus 90 and S .…”
Section: Discussionmentioning
confidence: 99%
“…Thrips on the whole have received relatively little attention regarding their bacterial communities. Previous studies have largely focused on the most frequently encountered bacterium (identified as a near- Erwinia species) within a single thrips species Frankliniella occidentalis 28 32 with a few studies on other species (i.e. Aptinothrips species 33 , Thrips tabaci 34 , Scirtothrips dorsalis 35 , Frankliniella fusca 36 and F .…”
Section: Introductionmentioning
confidence: 99%